2014
DOI: 10.1159/000358267
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Randomised Controlled Trial of Fish Oil-Based versus Soy-Based Lipid Preparations in the Treatment of Infants with Parenteral Nutrition-Associated Cholestasis

Abstract: Background: Infants receiving prolonged parenteral nutrition (PN) are at risk of PN-associated cholestasis (PNAC). This can progress to hepatic failure and death if PN cannot be discontinued. Fish oil-based parenteral lipid preparation (FOLP) has been shown to be beneficial in case studies. Objectives: (1) To evaluate whether FOLP could halt or reverse the progression of PNAC compared with soy-based parenteral lipid preparation (SLP) and (2) to assess the effects of FOLP on liver function and physical growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 14 publications
(43 reference statements)
4
75
0
1
Order By: Relevance
“…However, the only mortality case in the present study resulted from sepsis with parenteral nutrition-related liver failure. This patient died before our introduction of fish oil-based lipid preparation in parenteral nutrition which carries a lower risk to liver injury [18]. Total parenteral nutrition was required in 47 to 79% of neonates after operation for JIA, and dependency was significantly associated with the length of remaining small bowel [5][6][7].…”
Section: Discussionmentioning
confidence: 95%
“…However, the only mortality case in the present study resulted from sepsis with parenteral nutrition-related liver failure. This patient died before our introduction of fish oil-based lipid preparation in parenteral nutrition which carries a lower risk to liver injury [18]. Total parenteral nutrition was required in 47 to 79% of neonates after operation for JIA, and dependency was significantly associated with the length of remaining small bowel [5][6][7].…”
Section: Discussionmentioning
confidence: 95%
“…There have been efforts to prevent or reverse cholestasis by modifying lipid administration in patients requiring long‐term PN. Modifications include lipid minimization, temporarily discontinuing lipids, and using lipid emulsions containing lipid sources other than soybean oil (eg, pure fish oil or composite lipid emulsions with or without fish oil) …”
Section: Lipid Emulsions’ Role In the Treatment And Prevention Of Chomentioning
confidence: 99%
“…Multiple subsequent studies using various formulations of fish oil lipid emulsions have consistently demonstrated resolution of cholestasis in patients with IFALD. (3639)…”
Section: Intestinal Failure Associated Liver Disease (Ifald)mentioning
confidence: 99%